Imago Dei Pascabiologis: Pengunggahan Akal Budi sebagai Keberlanjutan Partisipasi - Gabriel Hotmartua Pardede; Frans Best Soma Marpaung (Indonesian Journal of Theology, 2026)
This article examines mind-uploading in transhumanism through a dialogue with Christian eschatological theology and the doctrine of the imago Dei, particularly concerning personal identity and the continuity of existence. By employing the concepts of futurum–adventus and creatio continua, mind-uploading is understood as an expression of human creative participation in the ongoing dynamics of creation, which remains continually open to the action of God as the giver of the future. Furthermore, through a dynamic reading of the imago Dei, this article proposes that post-biological entities embody both discontinuity and continuity of identity, as an “I and not-I” in an eschatological sense. These post-biological entities carry traces of the image of God in the form of relational patterns, memory, and self-expression that participate in history. This study thus proposes a rearticulation of the imago Dei within a post-biological context.